Cytokines profiles in cervical mucosa in patients with cervical high-risk human papillomavirus infection - De-Lai Long; Hua-Lin Song; Peng-Peng Qu (Journal of Infection in Developing Countries)
Introduction: The purpose of this study was to detect the expression of local cytokines in cervical mucosa between patients with transient and persistent HR-HPV infection with or without CIN.